Manejo da irrigação para produção de minimilho através do tanque classe A - Meneghetti, Adriana Maria (2005)
This research aimed on evaluating the growth and production of corn (Zea mays L.) in order to obtain the baby corn, which was submitted to the variation of four different depth irrigations, recorded from the culture s evapotranspiration, based on the class A, and applied when the evapotranspiration reached these following accumulated values: T1-15 mm, T2- 30 mm, T3- 45 mm e T4- 60 mm. The statistical model was outlinement completely with four treatments and five replications. Results were submitted to the statistical analysis, by the Sisvar program (FERREIRA 2000). The analysis of variance and the averages from the treatments were also recorded, as well as compared considering 5 % of probability according to the Tukey test and regression analysis. The experimental plots had about 8 m of length; the plants were separated by 0.080m among themselves and 0.70 m by rows, totalizing 100 plots to each plot. The features regarding the growth during the culture s cycle were: plant height (PE), foliar area (FA), leaf number (LN), foliar area index (FAI). Some other features were analyzed regarding the production analysis as: number of ear by plant (NEP), height of insertion of the first ear (HIFE), length of the ear with and without straw (LEWOS), diameter of the ear with and without straw (DEWOS), mass of the ear with and without straw (MEWOS), number of the row of grains by ear (NRGE) and number of ear, accomplishing 360 g. There were significant differences on production results regarding data of growing of foliar area and foliar area index. Significant differences had been also observed in the production of HIFE and LEWOS, and DEWOS, MEWOS and MEWOS, NRGE and number of ear that accomplishes 360 g. There was an increase in the depth irrigation and also in the application frequency, which implied in greater values of foliar area, as well as in the foliar area index, number of ear by plant, height of insertion of the first ear, number of row of grains by ear and number of ear, accomplishing 360 g, but also lower values for height, leaf number and length, diameter and ear s mass, with and without straw. The Best commercial results were recorded with T1 15 mm, when using 18 % of ear. The scheduling irrigation for baby corn must be carried out with application when the crop evapotranspiration indicates 15 mm and 30 mm accumulated values. It could also be understood with this trial that greater values cause reduction on productivity.